Creative Dance in the Education Curriculum: Justifying the Unambiguous - Bergmann, Sheryle (Canadian Journal of Education/Revue canadienne de l’éducation, 1995)
The inclusion of creative dance in the education curriculum has been variously justified in terms of its value as art, as movement, as therapy, and as a component of an integrated curriculum. Although creative dance is currently justified in different curricula for contra- dictory and ambivalent reasons, there is a need for an unambiguous inclusion of creative dance as a legitimate art form in the curriculum. I evaluate the various justifications for creative dance as movement, therapy, integration, and art and examine how these thwart or do not thwart the need for an unambiguous inclusion of creative dance as an art form. Pour justifier l’intégration de la danse créative dans les programmes scolaires, on invoque sa valeur comme art, comme mouvement et comme thérapie, ou encore sa place au sein d’un programme intégré. Il faut que la danse créative soit incluse d’une manière non ambiguë dans les programmes scolaires en tant qu’expression artistique ayant droit de cité. Actuellement, on justifie l’intégration de la danse créative dans divers programmes scolaires en faisant appel à des raisons contradictoires et ambivalentes. L’auteure évalue les divers moyens de justifier la danse créative comme mouvement, thérapie, intégration et art, et analyse comment ces diverses justifications vont ou non à l’encontre du besoin d’inclure sans ambiguïté dans les programmes scolaires la danse créative comme ex- pression artistique.